Environmental Graphic Design Of Karanggede Sismamedika Boyolali Hospital - Yudi Wibowo; Arif Yulianto; Ahmad Khoirul Anwar; Henny Tri Hastuti Hasana (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Karanggede Sismamedika Hospital carried out a brand identity redesign in 2021. Along with this brand identity redesign, renovations were also carried out on the building and its interior layout. This has implications for the emergence of new problems related to the brand image that must be immediately created for the building and its spatial layout. The aim of this research is to design an appropriate environmental graphic design concept as an effort to create a brand image through new spatial planning and realizing the concept into an environmental graphic design work that is in accordance with the brand identity of Karanggede Sismamedika Hospital. This research uses descriptive qualitative methods with data collection techniques of observation, interviews and literature study. The result of this research is a visual communication work that applies brand identity to the exterior and interior of Karanggede Sismamedika Hospital. The conclusion obtained from this research is that brand image can be realized if environmental graphic design pays close attention to aspects of aesthetics, function and user comfort.